Metastability of multi-lamellar vesicles in a nonionic system - Filippelli, L. (2015)
Nuclear magnetic resonance spectroscopy and rheological analysis have been used to investigate the stability of mechanically induced tri-ethylene-glycol-mono-n-decyl-ether (C(10)E(3))/deuterium oxide (D(2)O) multi-lamellar vesicles (MLVs) and the transition from MLVs to planar lamellae. It was found that MLVs prepared by vortex stirring, relax back to the lamellar phase in a few hours while the relaxation of the shear induced MLVs takes days. Pulsed gradient spin echo and water self-diffusion coefficient experiments, revealed that the MLVs texture, obtained by vortex stirring, is composed of large size structures. These data indicate that the kinetics of lamellar re-formation depend on the MLVs number density.